Identification and Quantification of an Adulterant in a Dietary Supplement Marketed for Sexual Enhancement - Flavia Redko; Sabrina Flor; Silvia Lucangioli; Jerónimo Ulloa; Rafael Ricco; Claudio Fernández; Luis Sambrotta; Liliana Muschietti (Journal of Advanced Pharmaceutical Science And Technology, 2018)
In recent years, the consumption of dietary supplements (DS) has increased worldwide. In Argentina, approximately 14 million DS units were sold between 2015 and 2017. The adulteration of DS with active pharmaceutical ingredients or their analogues has been reported. This represents an alarming emerging risk to public health. The aim of this work was to detect the possible adulteration of a DS marketed in Argentina for the treatment of erectile dysfunction. Initially, thin layer chromatography analysis of the DS capsules content suggested the presence of a major compound. For the isolation and purification of this compound, an easy method consisted of a liquid-liquid extraction (water/CH2Cl2) followed by re-crystallisation from ethanol, is reported. Spectroscopic techniques such as mono- and bidimensional nuclear magnetic resonance, Fourier transform infrared spectroscopy and mass spectrometry allowed its identification as tadalafil. A rapid and reliable method was developed for the quantification of tadalafil in this DS by high performance liquid chromatography-mass spectrometry (HPLC-MS/MS). The mean content of tadalafil per capsule was 21.2 mg which represents a slightly higher value than that found in approved products in Argentina (5 or 20 mg per tablet). In addition, an undeclared alga was identified in the DS by microscopic techniques.
Keywords: adulteration